The shale oil boom and the U.S. economy: Spillovers and time-varying effects - Hilde Christiane Bjørnland; Julia Zhulanova (Norges Bank, 2019)
We analyze if the transmission of oil price shocks on the U.S. economy has changed with the shale oil boom. To do so, we put forward a framework that allows for spillovers between industries and learning by doing (LBD) over time. We identify these spillovers using a time-varying parameter factor-augmented vector autoregressive (VAR) model with both state level and country level data. In contrast to previous results, we find considerable changes in the way oil price shocks are transmitted to the U.S economy: there are now positive spillovers to non-oil investment, employment and production from an increase in the oil price - effcts that were not present before the shale oil boom.
hdl:11250/2652836
Keywords: C11; C55; E32; E42; Q43; 330; Shale oil boom; Oil Prices; Time-varying factor-augmented VAR model; Spillovers; Geographical dispersion